Rose Bengal Immobilized on Supported Ionic‐Liquid‐like Phases: An Efficient Photocatalyst for Batch and Flow Processes. Issue 17 (25th July 2019) - Valverde, David; Porcar, Raul; Izquierdo, Diana; Burguete, M. Isabel; Garcia‐Verdugo, Eduardo; Luis, Santiago V.
Abstract: The catalytic activity of Rose Bengal (RB) immobilized on supported ionic liquid (IL)‐like phases was evaluated as a polymer‐supported photocatalyst. In these systems, the polymer was designed to play a pivotal role. The polymeric backbone adequately modified with IL‐like moieties (supported IL‐like phases, SILLPs) was not just an inert support for the dye but controlled the accessibility of reagents/substrates to the active sites and provided specific microenvironments for the reaction. The structure of SILLPs could be finetuned to adjust the catalytic efficiency of the RB‐SILLP composites, achieving systems that were more active and stable than the related systems in the absence of IL‐like units. Abstract : Immobilized Rose Bengal : Polymers containing imidazolium units are excellent and tunable supports enhancing the stability and activity of Rose Bengal as a photooxidation catalyst under batch and flow conditions.